0593 Hypoxemia During Sleep Disordered Breathing and Cardiovascular Disease: A Comparison of Different Oxygen Desaturation Measures. (27th May 2020) - Mazzotti, D R; Leppänen, T; Sands, S; Töyräs, J; Wellman, A; Kulkas, A; Redline, S; Karhu, T; Azarbarzin, A
Abstract: Introduction: The apnea-hypopnea index has been used to characterize obstructive sleep apnea (OSA) severity. However, this metric is limited in providing information about cardiovascular disease (CVD) risk. Recent studies proposed alternative metrics that capture frequency, duration, depth, and combinations of duration and depth of hypoxemia. This study provides a systematic evaluation of the association between conventional or novel nocturnal hypoxemia metrics and the incidence of CVD and CV mortality in the Sleep Heart Health Study (SHHS). Methods: We used data from 5, 042 participants of the SHHS. Over 10.7 years, there were 1, 312 (26.0%) incident CVD events and 359 (7.1%) CV deaths. We calculated standardized (z-scored) values of eight nocturnal hypoxemia indices, including conventional (e.g., oxygen desaturation index) and novel metrics (e.g., hypoxic burden, respiratory event-related area under desaturation curve and desaturation severity, corresponding to alternative quantitative measurements looking at the shape of each desaturation event). The association between each metric and incidence of CVD or CV mortality was evaluated using Cox proportional hazards models. Age, sex, body mass index, race, ethnicity, smoking, total sleep time, number of respiratory events, and prevalent CVD at baseline were used as covariates. Hazard ratios (HR) are presented as the effect of one standard deviation increase in each correponding metric. Results: In unadjusted models, all nocturnal hypoxemia indices were associated with increased incidence of CVD and CV mortality. In adjusted models, longer average desaturation duration was associated with lower CVD incidence (HR[95%CI]=0.93[0.86-0.99];p=0.034), higher hypoxic burden with increased CV mortality (HR[95%CI]=1.22[1.04-1.43];p=0.017), and higher % sleep time with oxygen saturation less than 90% (Tlt90%) with increased CV mortality (HR[95%CI]=1.12[1.00-1.26];p=0.040). Conclusion: Different metrics of nocturnal hypoxemia derived from polysomnography were associated with CV risk in the SHHS. However, after covariate adjustment, only shorter average desaturation duration, and higher hypoxic burden and Tlt90% were independent CV risk factors. Support: AASM Foundation (194-SR-18, 188-SR-17); American Heart Association (19CDA34660137); NIH (U01HL53940, U01HL53941, U01HL63463, U01HL53937, U01HL53938, U01HL53916, U01HL53934, U01HL63429, U01HL53931, HL114473, P01HL094307, HL134015, R35HL135818, 1R21HL145492-01, R01HL102321, R01HL128658); The State Research Funding (KUH: 5041767, 5041768; TUH: VTR3242, VTR3228, EVO2089), Academy of Finland (313697, 323536), Business Finland (5133/31/2018), Respiratory Foundation of Kuopio Region, Tampere Tuberculosis Foundation, Research Foundation of Pulmonary Diseases, Foundation of Finnish Anti-Tuberculosis Association.